Epigenetics and Hot Spots of Crime: rethinking the Relationship Between Genetics and Criminal Behavior - Leshem, Rotem (Journal of contemporary criminal justice, 2019)
There is a growing recognition of the importance of micro-geographic areas in the generation of crime problems. While many studies show that crime is heavily concentrated at crime hot spots, scholars have only begun to examine how living in such places affects human development. We point to an unexplored component of the relationship between living in a hot spot, and crime and violence. We argue that crime hot spots function as violent and stressful environments and thus have long-term, possibly intergenerational, impacts on brain development. It is proposed that living in such places may be associated with DNA methylation profiles related to aggressive behavior. In this context, the study of the epigenetic influences of crime hot spots has tremendous potential for advancing our understanding of crime and violence, as well as generating new approaches for crime prevention.